Applying student-generated theories about global change and energy demand. Issue 5 (2nd November 2015) - Ahamer, Gilbert
Abstract : Purpose: – The purpose of this paper is to explore how learning technology could be applied to the development of educational tools for global climate change. The task to be performed in an informed dialogue is to assess the causes and drivers for global climate change and to produce an improved basis of scientific understanding for the implementation of the climate protection targets suggested for each country. By character, this approach integrates the political and the scientific level. Design/methodology/approach: – The paper applies learning theories and options for educational technologies to socio-economic, technological, biospheric, political and scientific themes relevant to present climate change. Findings: – Drivers, effects and subsequent measures are subject to highly nonlinear effects. Thus, the combination of a (scientific, fact based) "Global Change Data Base" and a (dialogic, communication based) discourse (in the spirit of "Surfing Global Change") seems best suitable to produce solutions for the seemingly unresolvable issues of climate protection. This combination of approaches is entitled "Tackle the Task of a Transition through Technological Targets (T5)" and allows the application of hypotheses generated by students in a scaffolded setting of discursive learning. Social implications: – Suggestions for CO2 abatement measures are currently passing the process of political negotiation in all countries in the world. The different views and patterns of ethical values are harmonised during the T5 learning process and symbolise the required political process of consensus finding among and between different ministries, countries and global interest groups. Originality/value: – This approach includes social and natural driving factors such as population, land use, economics, politics, energy systems, the global carbon cycle, biosphere and climate, and thus offers a more comprehensive learning endeavour than many other approaches.